Put-Call Ratio volume vs. open interest in predicting market return: A frequency domain rolling causality analysis - Sangram Keshari Jena; Aviral Kumar Tiwari; Amarnath Mitra (Economies, 2019)
This study examined the efficacy of the Put-Call Ratio (PCR), a widely used information ratio measured in terms of volume and open interest, in predicting market return at different time scale. Volume PCR was found to be an efficient predictor of the market return in a short period of 2.5 days and open interest PCR in a long period of 12 days. Thus, traders and portfolio managers should use the appropriate PCR depending upon the time horizon of their trade and investment. The results are robust even after controlling for the information generated from the futures market.
Keywords: 330; Put-Call Ratio; volume; open interest; frequency-domain roiling causality